2010
DOI: 10.4161/auto.6.8.13547
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 transcriptional factor activated by reactive oxygen species induces IL6 in starvation-induced autophagy of cancer cells

Abstract: Autophagy is one of the survival processes of cancer cells, especially in stressful conditions such as starvation, hypoxia and chemotherapeutic agents. However, its roles in tumor survival have not yet been fully elucidated. Here, we found for the first time that JAK2/STAT3 was activated in HeLa cells when they were starved or treated with rapamycin. STAT3 activation was associated with autophagic processes, because it was completely inhibited by 3-methyladenine, partially inhibited by knockdown of molecules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 35 publications
11
96
1
Order By: Relevance
“…We recently observed that Jak2/STAT3 pathway was activated in both starvation and rapamycin treatment of cancer cells. However, IL6 was induced only in starved cells but not in rapamycin-treated cells (Yoon et al, 2010). As there was clear difference between the two models of autophagy, we were able to find in the present work that NF-kB was activated only in starvation, thus contributing to full IL6 induction in collaboration with activated STAT3.…”
Section: Introductionsupporting
confidence: 49%
See 3 more Smart Citations
“…We recently observed that Jak2/STAT3 pathway was activated in both starvation and rapamycin treatment of cancer cells. However, IL6 was induced only in starved cells but not in rapamycin-treated cells (Yoon et al, 2010). As there was clear difference between the two models of autophagy, we were able to find in the present work that NF-kB was activated only in starvation, thus contributing to full IL6 induction in collaboration with activated STAT3.…”
Section: Introductionsupporting
confidence: 49%
“…In the previous study, we found that Jak2/STAT3 was activated in amino-acid-and serum-deprived cancer cells, as well as rapamycin-treated cancer cells (Figure 1a), which was totally dependent on ROS produced by NADPH oxidase enzymes that were activated during early autophagic processes (Yoon et al, 2010). Activated STAT3 contributed to the induction of IL6 cytokine mRNA and its protein secretion only in starved cancer cells but not in rapamycin-treated cancer cells (Figures 1b and c), indicating that additional signals for full induction of IL6 were lacking in rapamycin-induced autophagy of cancer cells.…”
Section: Nf-kb Activation Is Required For Il6 Induction In Starved Camentioning
confidence: 72%
See 2 more Smart Citations
“…The presence of excessive ROS can cause fatal cellular lesions by damaging cellular proteins, lipids and DNA [35]. ROS are associated with various transcription factors, such as NF-B [36], activator protein-1 (AP-1) [37], hypoxiainducible factor-1 [38] and signal transducer and activator of transcription 3 (STAT3) [39], which are involved in inflammation, cellular transformation and tumor biology. Furthermore, ROS also control the expression of various tumor suppressor genes, such as phosphatase and tensin homolog (PTEN) [40].…”
Section: The Microenvironment Of "Acquired Lymphoid Tissue"mentioning
confidence: 99%